The Implementation of Transportation and Transit Projects on the Basis of Public-Private Partnership in Russia - Tsevtkov, Valery Anatolyevich; Zoidov, Kobilzhon Khodzhievich; Medkov, Alexey Anatolyevich (Economy of Regions, 2016)
The article considers the main directions of the implementation of the current transportation and transit projects on the basis of the institution of public-private partnership in Russia. This work is a continuation of the study of the theory and practice of the application of public-private partnership in the investment projects aimed at the development and realization of the transportation and transit potential of the country. On the methodological basis of evolutionary and institutional economics, historical approach, system-oriented analysis and the theory of firms, the main current projects for the development of Russian transportation and transit system using public-private partnership are considered. They are the construction of a high-speed line of Moscow - Kazan with subsequent extension to the Chinese border; functioning of the transport and logistics in the Chelyabinsk region; infrastructure of transit cargo by Northern Sea Route; participation of foreign investors in the development of Russian seaports and sea gates. It is shown that the competitive advantage of transit traffic by a particular route requires more traversing speed of cargo with a minimum of stops, handling and overloads in the way. Revenue from transportation and transit potential implementation can be comparable to the size of the resource rent in the case of the development in Russia of the production and transit sector of the economy, and not only of a transit one. In this regard, the emphasis is placed on the determination of the possibility and necessity of organizational changes associated with the development of a large public-private transportation company, able to compete with global sea container services of the route of Asia - Europe. The main directions and activities under the proposed national project «Development of transit economy in Russia: Uniting Eurasia» and its subprogram «Creation of innovative rolling stock for container and multimodal transport» are developed. The results of the study can be used in the preparation of state programs and projects, containing a system of measures to develop and implement the transportation and transit potential of Russia on the basis of institutional and organizational changes.